EXPLORING IMPULSE BUYING TRIGGERS : A COMPREHENSIVE INVESTIGATION OF VISUAL MERCHANDISING, PRODUCT DIVERSITY, AND HEDONIC SHOPPING MOTIVATION AT MR. DIY JEPARA STORE - Safitri, Hera Yuliana; Arifin, Samsul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research intends to figure out the influence of visual merchandising, product diversity, and hedonic shopping motivation on impulse buying among visitors to the Mr. DIY Jepara store. This study employs a quantitative approach, utilizing a questionnaire as the research instrument and employing a double regression analysis tool. The sampling method applied is accidental sampling, involving a total of 96 respondents. The analysis of data is conducted through quantitative means, utilizing the SPSS 26 program. The research findings indicated that visual merchandising (X1) exerted a partially positive and significant impact on impulse buying behavior among visitors at Mr. DIY Jepara's store. The variety of products (X2) demonstrated a partially positive and significant effect on the impulsive buying tendencies of visitors to Mr. DIY Jepara's store. Additionally, hedonic shopping motivation (X3) was found to have a partially positive and significant influence on impulsive buying behavior among the store's visitors. When considered collectively, the three independent variables collectively exhibited a positive and significant impact on impulsive buying among visitors at Mr. DIY Jepara's shop.